The age of miracles : a novel - Walker, Karen Thompson (Random House, 2012)
Imagines the coming-of-age story of young Julia, whose world is thrown into upheaval when it is discovered that the Earth's rotation has suddenly begun to slow, posing a catastrophic threat to all life.